The Cognitive Impact of Artificial Intelligence on the Spread of Fake News through Social Media: Public Perceptions and Democratic Resilience (Journal of Asian Development Studies, 2025)
This study investigates the cognitive impact of Artificial Intelligence (AI) on the spread of fake news via social media, focusing on public perceptions and democratic resilience. In an era where AI is emerging technology and used to generate and amplify disinformation, understanding its influence on public opinion and trust in democratic institutions is crucial. There remains a significant gap in empirical research that quantifies how AI-driven fake news affects public perception and the capacity of democratic societies to withstand such manipulation. Using a structured quantitative research design, data was collected through a survey administered to 250 participants across diverse disciplines and academic backgrounds from the university of Karachi. The data were analyzed using descriptive statistics and regression analysis to explore correlations and causal relationships. The findings reveal a strong correlation between high exposure to AI generated fake news content based on posts, videos and images leading to mistrust in public and democratic institutions. AI has been widely used in spreading of the fake news particularly AI made videos of the political or social media influencer. AI algorithm is more involved in consensus development in political context. However, digital literacy and critical thinking skills served as significant protective factors against AI based misinformation. The study recommends implementing comprehensive media literacy programs, stricter AI content regulation policies, and public awareness campaigns to enhance democratic resilience.